Detection of Novel US Neisseria meningitidis Urethritis Clade Subtypes in Japan - Takahashi, Hideyuki; Morita, Masatomo; Yasuda, Mitsuru; Ohama, Yuki; Kobori, Yoshitomo; Kojima, Munekado; Shimuta, Ken; Akeda, Yukihiro; Ohnishi, Makoto (Emerging infectious diseases, 2023)
Neisseria meningitidis causes invasive meningococcal diseases and has also been identified as a causative agent of sexually transmitted infections, including urethritis. Unencapsulated sequence type 11 meningococci containing the gonococcal aniA-norB locus and belonging to the United States N. meningitidis urethritis clade (US_NmUC) are causative agents of urethral infections in the United States, predominantly among men who have sex with men. We identified 2 subtypes of unencapsulated sequence type 11 meningococci in Japan that were phylogenetically close to US_NmUC, designated as the Japan N. meningitidis urethritis clade (J_NmUC). The subtypes were characterized by PCR, serologic testing, and whole-genome sequencing. Our study suggests that an ancestor of US_NmUC and J_NmUS urethritis-associated meningococci is disseminated worldwide. Global monitoring of urethritis-associated N. meningitidis isolates should be performed to further characterize microbiologic and epidemiologic characteristics of urethritis clade meningococci.